Cephalometric Evaluation of Skeletal and Dental Effects of Modified Facemask - Amjad Al Taki; Toros Alcan; Korkmaz Sayınsu (Galenos Yayinevi, 2006)
The aim of this study was to examine the effects of the newly modified maxillary protraction facemask. 15 patients, having an average age of 12.42 ± 1.87 years, presenting Class III malocclusion with maxillary retrognathism were treated for 7.5 ± 1.02 months. Rapid palatal expansion was performed for 7 days with a full coverage acrylic cap splint type appliance. At the 7th day, protraction therapy was started with the combination of a specially designed face bow and Petit type facemask. The face bow was bent upward to raise the point of force application to pass through the center of resistance of the maxilla. A total of 1000 g (500 g on each side) of protrusive force was applied and the patients were instructed to wear the facemask for 16 h/day. Wilcoxon signed rank test was carried out to evaluate 48 parameters measured on cephalometric radiographs. Results showed that the maxilla was displaced anteriorly without rotation. Maxillary occlusal plane showed a clockwise rotation. Maxillary incisors were extruded and retroclined. Mandible was displaced downward and backward. In conclusion, by introducing our new face bow design, we were able to protract the maxilla bodily and at the same time to have a more effective force-moment system where the whole protractive force was utilized in protracting the maxilla.